2017
DOI: 10.4236/ojog.2017.71011
|View full text |Cite
|
Sign up to set email alerts
|

Midwives’ Professional Satisfaction and the Quality of Obstetric Care in Developing Country

Abstract: Introduction: In Africa, poor working conditions affect the motivation of health care providers. The objective is to study midwives' professional satisfaction on the technical quality of emergency obstetric care in Senegal. Material and Methods: This was a prospective study of 16 hospitals in Senegal. The job satisfaction of midwives was measured during a personal interview. The instrument used was validated in Senegal and Mali. Other data collected relate to professional and institutional characteristics. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Studies indicate that the existence of the language barrier has shown to be a threat to the quality of hospital care. 28,29 The non-English speaking population utilises a growing volume of healthcare services and thus comes into contact with nurses daily. Literature alluded to that some of the adverse events that occur within the maternity units, may be related to the language barrier as a result of communication difficulty between midwife and patient, adverse events reported were associated with language barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that the existence of the language barrier has shown to be a threat to the quality of hospital care. 28,29 The non-English speaking population utilises a growing volume of healthcare services and thus comes into contact with nurses daily. Literature alluded to that some of the adverse events that occur within the maternity units, may be related to the language barrier as a result of communication difficulty between midwife and patient, adverse events reported were associated with language barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, we collect money ourselves and fix it using our money." (23) "Due to the hospital designated as the main referral center [of the province], many patients come in the worst condition, but (maternity) ICU are very limited. Sometimes, the patients are told that the (maternity) ICU are full, but the patients Published by Sciedu Press still want to be here even though they have to sign the consent that they accept any situation as the impact of not being in the (maternity) ICU ."…”
Section: Shortage Of Resources To Provide Health Servicesmentioning
confidence: 99%
“…(23) "Educational background of the patients and their family is too low; even if we have explained [something] very clearly, they still don't understand and ask again and again." (34) 3.2.5 Challenges teaching students Indonesian midwives faced two main challenges in teaching students.…”
Section: Shortage Of Resources To Provide Health Servicesmentioning
confidence: 99%
See 1 more Smart Citation